Chronotope Dynamics in M. Yu. Lermontov’s Poem Alone I Set out on the Road - Kroó, Katalin (Izvestiâ Uralʹskogo federalʹnogo universiteta. Seriâ 2, Gumanitarnye nauki, 2020)
In this paper, the author studies the chronotope dynamics in Lermontov’s lyric poem Alone I Set out on the Road… in order to reveal the meaning-generation processes (the so-called “semantic plot” and its ramifications) in the evolution of the lyrical character’s spiritual trajectory, who is on his “meditative philosophical journey” (O. V. Zyryanov) and gradually transforms into the lyrical subject of the poetic text. The interpretation is based on the segmentation of the chronotope system into its main components, with the description of their correlation, whose dynamics defines the position of the lyrical character and the subject of the text in their process of transformation. This aims at clarifying the multi-valency of the system of spatial and temporal elements developing according to a logic contradicting the conceptualisation of dichotomic connections and an interpretative movement in the exclusive terms of thesis — antithesis — synthesis. In Lermontov’s lyrical text, within their motif development, both the upper and the lower spatial spheres are semantically doubled (cf. the earth, the desert, the sky, heavens), while the correlations between these and other elements forming an overall global space, as a consequence of each being addressed intensively by the lyrical character/subject in his role as an active initiator (agent) of chronotopic/textual communication, outline the character’s successful conquest of the total chronotope system as a whole universe, in which spiritual omnipraesentia is achieved. Instead of a model of unification with nature or another pre-existing ideal world ready to offer itself to be acquired through life/text experience, the poem elaborates a model of creation of spirituality in such forms as the acquisition of metaphysical values of existence which are bound to the earth as the centre of primary experience. There, human creative force in cultural eternity creates forms of mediation linking the internal and the external, the lower and the upper spheres, the human and the conceptualisation of divine essence, and also direct life experience and its textual transfiguration. All of these emerge in the chronotope system of Lermontov’s poem.